Money - Robertson, Dennis Holme (New York : Pitman Pub. Corp., 1948)
The book examines the merits and drawbacks of money, the value of money, the quantity of money and other issues revolving around money as a medium of exchange.
usc 29/06/2017
Loans
Keywords: Money; Value; Prices; Foreign exchange